African Development in the New Millennium: Going Beyond the "Good Governance" Debate - 1Oluseyi Elijah AKINBODE / 2’Bimbo Ogunbanjo, PhD ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Africa is a rapidly changing continent. But for many, it is still an unknown place, shrouded by myths and distorted perceptions. Africa is in many ways still a marginalized continent. But things are certainly changing, and are going to change much more in the near future. This paper examines the debate surrounding the issue of ‘good governance’ and whether it is actually good for development. It offers a concise summary of literature and evidence in the three areas: the ‘good governance’ agenda as it has affected Africa, the research-based response to this, and the implications for Africa’s economic transformation. Thus, the second section discusses the origins of the concern about governance quality in Africa between the 1970s and the 1990s; the third section reviews the rebuttals and reformulations that have led the scholarly debate since the turn of the millennium; the fourth section applies the findings to the challenge of moving Africa on from economic growth to economic transformation; and the fifth section concludes that comprehensive governance improvement is not necessarily a precondition for economic progress in developing Africa.